2023
DOI: 10.1007/s11270-023-06148-4
|View full text |Cite
|
Sign up to set email alerts
|

Solar Photocatalysis for the Decontamination Of Water from Emerging Pharmaceutical Pollutant Chloroquine Using Nano ZnO as the Catalyst

Abstract: Photo-driven advanced oxidation process (AOP) with pharmaceutical wastewater has been poorly investigated so far. This paper presents the results of an experimental investigation on the photocatalytic degradation of emerging pharmaceutical contaminant chloroquine (CLQ) in water using zinc oxide (ZnO) nanoparticles as the catalyst and solar light (SL) as the source of energy. The catalyst was characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), scanning electron microscopy-energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The initial increase in the degradation efficiency is attributed to the availability of additional active sites for the reaction owing to the higher concentration of the catalyst. However, as the amount of the catalyst increases further, the degradation rate decreases due to the aggregation of catalyst particles, which reduces the accessibility of the active sites for organic pollutants . Furthermore, excess catalysts can hinder light penetration, impeding the effective utilization of UV irradiation and subsequently reducing the degradation efficiency (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The initial increase in the degradation efficiency is attributed to the availability of additional active sites for the reaction owing to the higher concentration of the catalyst. However, as the amount of the catalyst increases further, the degradation rate decreases due to the aggregation of catalyst particles, which reduces the accessibility of the active sites for organic pollutants . Furthermore, excess catalysts can hinder light penetration, impeding the effective utilization of UV irradiation and subsequently reducing the degradation efficiency (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…A key characteristic of advanced oxidation processes (AOPs) is the production of highly reactive hydroxyl radicals, which possess superior oxidative power compared to ozone and hydrogen peroxide. This feature has facilitated the accelerated degradation of organic pollutants [ 12 , 13 ]. Consequently, AOPs have gained prominence and have become preferred alternatives over traditional water treatment methods, due to their remarkable success in effectively degrading organic pollutants [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, AOPs have gained prominence and have become preferred alternatives over traditional water treatment methods, due to their remarkable success in effectively degrading organic pollutants [ 14 ]. Among the various AOP methods, photocatalysis and its various adaptations have emerged as the most promising technique for industrial applications [ 13 ]. Semiconductor oxides, particularly ZnO and its nanocomposites, have been extensively investigated and widely employed as catalysts in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The charge trapping sites formed help to diffuse highly energetic electrons from the conduction band (CB) into the network structure of metal dopants, which eventually delay e – /h + recombination . Au is a potential dopant due to its high stability and nonreactivity and it could also insert new energy levels by equivalent substitution of Ti (atomic radius 0.147 nm) with Au (atomic radius of 0.147 nm). , Few studies reported on Au doping onto TiO 2 using toxic chemicals of environmental concern. , The bio-based methods are eco-friendly and environmentally benign. It could improve the surface properties and increase the number of defects in metal-doped photocatalysts to enhance their activity.…”
Section: Introductionmentioning
confidence: 99%